EFFECTIVENESS OF A COMBINED MINIMALLY INVASIVE STRATEGY FOR EARLY CHILDHOOD CARIES PREVENTION: A PROSPECTIVE CONTROLLED CLINICAL STUDY - Qudratov Abbos Farhod o'g'li; Abdusattarov Abbosxon Abdubosit o’g’li (American Journals Publishing, 2026)
Early childhood caries (ECC) remains one of the most prevalent chronic diseases in pediatric populations worldwide and continues to pose a significant clinical and public health challenge. Although individual minimally invasive interventions have demonstrated effectiveness in controlling early carious lesions, limited evidence exists regarding the clinical impact of integrated, risk-based minimally invasive models that simultaneously address caries activity, lesion progression, and patient-related behavioral outcomes.
Keywords: Early childhood caries; minimally invasive dentistry; risk-based model; silver diamine fluoride; atraumatic restorative treatment; pediatric dentistry